Science teaching styles and students intrinsic motivation: validating a structural model - Syed Hassan, Sharifah Sariah (s.n, 2012)
This present study seeks to investigate the teaching styles adopted by the science teachers and their student intrinsic motivation in order to be persistence in learning the subject. The purpose of the study was to validate the 5Es model and intrinsic motivation.